A Hybrid Approach to Estimating the Efficiency of Public Spending on Education in Emerging and Developing Economies - Grigoli, Francesco (IMF Working Papers; Working Paper ;, 2014)
The measurement of the efficiency of public education expenditure using parametric and non-parametric methods has proven challenging. This paper seeks to overcome the difficulties of earlier studies by using a hybrid approach to measure the efficiency of secondary education spending in emerging and developing economies. The approach accounts for the impact of the level of development on education outcomes by constructing different efficiency frontiers for lower- and higher-income economies. We find evidence of large potential gains in enrollment rates by improving efficiency. These are largest in lower-income economies, especially in Africa. Reallocating expenditure to reduce student-to-teacher ratios (where these are high) and improving the quality of institutions (as measured by the "governance effectiveness" indicator in the World bank's Governance Indicators database) could help improve the efficiency of education spending. Easing the access to education facilities and reducing income inequality (as measured by the Gini coefficient) could also help improve efficiency.